Decoding technological frames: a qualitative inquiry into business analytics perspectives - Keskin, Halit; Akgun, Ali Ekber; Tatoglu, Ekrem; Basaran, Hatice Tuba Etlioglu (TAYLOR & FRANCIS LTD, 2024)
Technological frames, examined through the lenses of social construction of technology (SCOT) and social cognition, are pivotal in organisational research. This study presents a comprehensive literature review from SCOT and social cognition perspectives, offering nuanced insights into how individuals perceive and interpret technology. Employing an exploratory qualitative approach, we conducted semi-structured interviews with professionals from diverse industries, chosen for their varied expertise. Through content analysis, we identified eight technological frame domains: affective and cognitive dimensions, application value, personal attitude, job-related factors, managerial and organisational influence, and colleagues' impact. Our inquiry delves into the intricate factors shaping these frames, highlighting influences at both individual and organisational levels. Crucially, this study underscores the relevance of its findings for business analytics and technology management, illuminating cognitive and affective dimensions that significantly impact technology adoption and organisational outcomes.
Keywords: Technological frame; emotional framing; SCOT; social cognition; business analytics; qualitative research; INFORMATION-TECHNOLOGY; SOCIAL CONSTRUCTION; MANAGEMENT; INNOVATION; PERFORMANCE; SOCIOLOGY; EVOLUTION; COGNITION; ADOPTION; COMPANY; Computer Science; Operations Research & Management Science